2019
DOI: 10.1038/s41598-018-36959-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcite fibre formation in modern brachiopod shells

Abstract: The fibrous calcite layer of modern brachiopod shells is a hybrid composite material and forms a substantial part of the hard tissue. We investigated how cells of the outer mantle epithelium (OME) secrete calcite material and generate the characteristic fibre morphology and composite microstructure of the shell. We employed AFM, FE-SEM, and TEM imaging of embedded/etched, chemically fixed/decalcified and high-pressure frozen/freeze substituted samples. Calcite fibres are secreted by outer mantle epithelium (OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…cell cytoskeletons) with properties such as structural support and repetitive energy dissipation. [8][9][10][11][12][13] For example, a-helical lamin protein domains that define the lattice-like network of the cell's nucleus, provide both crucial structural support, as well as aiding in the coupling of mechanical signals to complex biochemical processes in the cell. 14 The staggered architecture in a collagen microfibril permits energy dissipation through molecular sliding, rather than snapping and can withstand GPa of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…cell cytoskeletons) with properties such as structural support and repetitive energy dissipation. [8][9][10][11][12][13] For example, a-helical lamin protein domains that define the lattice-like network of the cell's nucleus, provide both crucial structural support, as well as aiding in the coupling of mechanical signals to complex biochemical processes in the cell. 14 The staggered architecture in a collagen microfibril permits energy dissipation through molecular sliding, rather than snapping and can withstand GPa of pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the corresponding extrapallial space must be relatively wide and variable in thickness. This is unlike bivalves [18] and rhynchonelliform brachiopods [19], in which some microstructures are produced across extremely thin (100 nm or less) extrapallial spaces. Accordingly, the crystals can protrude only by a matter of tens of nanometres.…”
Section: Discussionmentioning
confidence: 94%
“…Through many studies of brachiopod shell structure, Williams proposed that the different layers of the shell are produced by a single cell via a conveyor belt system (Williams, 1953(Williams, , 1966(Williams, , 1968a(Williams, , 1968bWilliams and Rowell, 1965). In contrast, a recent study proposed that more than one cell participates in the precipitation of a single calcite fiber/crystal, suggesting that calcite fibers are formed via ion transport of calcium (along with trace/minor elements) and carbonate rather than forming elsewhere in the epithelium and being transported and secreted by cell vacuoles (Simonet Roda et al, 2019). Additionally, while Simonet Roda et al (2019) did not find evidence of a metastable, amorphous calcium carbonate (ACC) precursor to brachiopod calcite, ACC has been observed in one study of a rhychonelliform brachiopod (Griesshaber et al, 2009), while other researchers found that brachiopod shell fibers are composed of calcite nanospheres or granules.…”
Section: Brachiopod Biomineralization and Potential Effects On δ 7 LImentioning
confidence: 88%